2020
DOI: 10.1177/2378023120948713
|View full text |Cite
|
Sign up to set email alerts
|

Soldiers to Scientists: Military Service, Gender, and STEM Degree Earning

Abstract: The authors use 2014–2018 data from the American Community Survey to answer two questions: To what extent is military service associated with higher rates of earning a bachelor’s degree in a science, technology, engineering, and mathematics (STEM) field (vs. a non-STEM field)? To what extent is this relationship gendered? The findings suggest that military service is associated with higher odds of completing a STEM degree and that this association is particularly strong for female veterans. Comparison across m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Analyses of American Community Survey data (ACS 2014–2018) presented here extend extant research, suggesting that even though a positive association between military service and STEM outcomes exists for women (Steidl et al, 2020; Werum et al, 2020), the same cannot be said universally for underrepresented minorities. In fact, among several groups of male veterans, intersectional patterns exacerbate classic disparities regarding STEM degrees earned.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Analyses of American Community Survey data (ACS 2014–2018) presented here extend extant research, suggesting that even though a positive association between military service and STEM outcomes exists for women (Steidl et al, 2020; Werum et al, 2020), the same cannot be said universally for underrepresented minorities. In fact, among several groups of male veterans, intersectional patterns exacerbate classic disparities regarding STEM degrees earned.…”
Section: Introductionsupporting
confidence: 53%
“…Second, previous research has documented the underrepresentation of women and racial minorities in STEM (Flowers & Banda, 2015;Hanson, 2013;Kim et al, 2009;Riegle-Crumb et al, 2019;Whitten et al, 2007). And finally, previous research has shown a consistently positive association between military service and STEM degree earning, especially for women (Steidl et al, 2020;Werum et al, 2020). Thus, we expected to find that military service would similarly be associated with higher rates of STEM degree earning among Black and Hispanic veterans, in particular.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Next, I introduce interaction terms in the models to examine the extent to which the odds of owning a firearm based on individual-level political identities are moderated by the political party of the president (H1b). To better understand the effect of the interaction terms on gun ownership-a binary measurefigures are developed by plotting the predicted probabilities (Steidl et al 2020). All results are reported in odds ratios (ORs), and robust standard errors are employed.…”
Section: Analytic Methodsmentioning
confidence: 99%
“…To better understand the effect of the interaction terms on gun ownership—a binary measure—figures are developed by plotting the predicted probabilities (Steidl et al. 2020). All results are reported in odds ratios (ORs), and robust standard errors are employed.…”
Section: Methodsmentioning
confidence: 99%